2011
DOI: 10.1007/s00122-011-1531-x
|View full text |Cite
|
Sign up to set email alerts
|

HvFT1 (VrnH3) drives latitudinal adaptation in Spanish barleys

Abstract: In barley, three genes are responsible for the vernalization requirement: VrnH1, VrnH2 and VrnH3. The winter growth habit of barley requires the presence of a recessive VrnH1 allele, together with an active VrnH2 allele. The candidate for VrnH3 (HvFT1) has been recently identified, with evidences pointing at a central role in the integration of the vernalization and photoperiod pathways. Functional polymorphisms have been proposed, but experimental evidence of their role on agronomic performance and adaptation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
53
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 44 publications
8
53
0
Order By: Relevance
“…Yan et al (2006) found an association between growth habit and mutations in the first intron, but the sequencing of the HvFT1 alleles from populations previously used to map QTL for flowering time (Hemming et al, 2008) failed to reveal any significant association between the two linked SNPs in intron 1 and flowering time. Further results reported in other surveys of HvFT1 allelic variation (Cuesta-Marcos et al, 2010; Casas et al, 2011) were also in disagreement with Yan et al (2006) regarding the direction of the effect assigned to the functional polymorphism in the first intron. Yan et al (2006) also identified two promoter haplotypes, characterized by seven linked SNPs and two indels in the first 550 bp upstream of the start codon.…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…Yan et al (2006) found an association between growth habit and mutations in the first intron, but the sequencing of the HvFT1 alleles from populations previously used to map QTL for flowering time (Hemming et al, 2008) failed to reveal any significant association between the two linked SNPs in intron 1 and flowering time. Further results reported in other surveys of HvFT1 allelic variation (Cuesta-Marcos et al, 2010; Casas et al, 2011) were also in disagreement with Yan et al (2006) regarding the direction of the effect assigned to the functional polymorphism in the first intron. Yan et al (2006) also identified two promoter haplotypes, characterized by seven linked SNPs and two indels in the first 550 bp upstream of the start codon.…”
Section: Introductionmentioning
confidence: 77%
“…This variation has been linked to differences in flowering phenotypes in a number of studies (Yan et al, 2006; Hemming et al, 2008; Casas et al, 2011). It seems clear now that, in Arabidopsis , the FT promoter and first intron contain cis-regulatory sites that are important for its transcriptional regulation (Tiwari et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations